SCM Prototype Design Using Economic Order Quantity (EOQ) Method to Improve Decor Material Inventory Performance - Dina Triana; Muhammad Iqbal; Rohminatin Rohminatin (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
The decoration industry is experiencing rapid growth along with the increasing public demand for decoration services for homes, cafes, commercial spaces, and various other aesthetic needs. This growth requires companies to have an effective inventory management system to ensure the availability of decorative materials and ensure optimal operational processes. However, actual conditions at Rahani Homedecor show that inventory management is still carried out manually, resulting in various problems, such as delays in stock recording, difficulties in monitoring stock availability, suboptimal procurement processes, and a high risk of excess or shortage of inventory. This study aims to design a Supply Chain Management (SCM) prototype using the Economic Order Quantity (EOQ) method to improve the performance of decorative material inventory management. The research method used is a descriptive qualitative approach through observation, interviews, and analysis of ongoing business processes. The EOQ method is applied to determine the optimal order quantity so that the procurement process can be carried out in a more planned and economical manner, while the SCM concept is used to integrate the flow of information between inventory, suppliers, and the purchasing process. The results show that the EOQ-based SCM prototype can help inventory management become more structured, organized, and easily controlled. The system developed facilitates user management of product data, supplier data, and purchasing transactions in a computerized manner, resulting in faster and more efficient work. Furthermore, the application of the EOQ method helps companies determine optimal order quantities based on inventory needs. Based on these results, it can be concluded that the application of SCM with the EOQ method can improve the effectiveness and efficiency of decorative material inventory management and support the smooth operation of the company.